The impact of obesity on female infertility - summary of current knowledge - Jastrzębska, Izabela; Sysło, Oliwia; Goliat, Weronika; Haraziński, Konrad; Rubik, Nikola; Gmur, Maksym; Gajewski, Michał; Sławińska, Barbara; Błecha, Zuzanna; Tacka, Nicole (Quality in Sport, 2025)
Introduction and Purpose: Obesity as a disease of civilization has become a new global epidemic. It is affecting a reduced quality of life. As its prevalence increases, the number of women of childbearing age who are overweight and consequently obese is also increasing. As a result, the number of cases with reproductive disorders is increasing. In addition, the topic of a syndrome that combines these two problems, which is polycystic ovary syndrome, is emerging with increasing frequency. This is becoming a challenge for physicians dealing with infertility treatment, pregnancy maintenance, miscarriages and pregnancy complications. This study aims to review current scientific research on the impact of obesity on female fertility and describe currently available treatment options for this group of women. Brief Description of the State of Knowledge: Adipose tissue influences gonadal function by secretion of adipokines, such as leptin, adiponectin, ghrelin and resistin. [1] Adipokines are important modulators of glucose metabolism, because they may primarily contribute to adverse fat distribution, altered appetite and satiety, impaired insulin sensitivity or insulin secretion, and to inflammation [2]. Adipokines contribute to metabolic syndrome, insulin resistance, and hyperandrogenism. This predispose patients to PCOS and associated infertility [3]. Summary: Obesity is an increasingly common challenge in infertility clinical practice. Assessing the impact of this disease on female infertility can provide valuable diagnostic and therapeutic information, potentially improving fertility in women at risk. Materials and Evidence: A literature review was conducted using the PubMed database.